2021
DOI: 10.3389/fpls.2021.645030
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking the Mustard-Oil Bomb: How a Glucosinolate-Sequestering Flea Beetle Copes With Plant Myrosinases

Abstract: Myrosinase enzymes play a key role in the chemical defense of plants of the order Brassicales. Upon herbivory, myrosinases hydrolyze the β-S-linked glucose moiety of glucosinolates, the characteristic secondary metabolites of brassicaceous plants, which leads to the formation of different toxic hydrolysis products. The specialist flea beetle, Phyllotreta armoraciae, is capable of accumulating high levels of glucosinolates in the body and can thus at least partially avoid plant myrosinase activity. In feeding e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…However, compared to the midgut, the foregut is a poorly studied part of the insect digestive system and has been largely excluded from studies of active uptake of hydrophilic compounds. Adults of P. armoraciae were previously shown to absorb a major proportion of ingested glucosinolates within a few minutes from the gut, which demonstrates that glucosinolates are taken up in the anterior part of the digestive tract with an efficient and fast mechanism (Sporer et al, 2021). In this study, we detected ingested glucosinolates in the beetle body when the corresponding plant material was still in the foregut, suggesting that these glucosinolates have been absorbed across the foregut epithelium within less than 1 min after oral uptake (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to the midgut, the foregut is a poorly studied part of the insect digestive system and has been largely excluded from studies of active uptake of hydrophilic compounds. Adults of P. armoraciae were previously shown to absorb a major proportion of ingested glucosinolates within a few minutes from the gut, which demonstrates that glucosinolates are taken up in the anterior part of the digestive tract with an efficient and fast mechanism (Sporer et al, 2021). In this study, we detected ingested glucosinolates in the beetle body when the corresponding plant material was still in the foregut, suggesting that these glucosinolates have been absorbed across the foregut epithelium within less than 1 min after oral uptake (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, feeding experiments with the myrosinase-deficient Arabidopsis tgg1/tgg2 mutant and wild type plants indicate that plant myrosinases reduced the glucosinolate sequestration rate by the insect in adult beetles [99]. Further analysis revealed that P. armoraciae can inactivate plant myrosinases in the gut to both reduce glucosinolate hydrolysis and promote their sequestering [99].…”
Section: Countering and Exploiting The Mustard Oil Bomb By Pests And Pathogensmentioning
confidence: 99%
“…Interestingly, feeding experiments with the myrosinase-deficient Arabidopsis tgg1/tgg2 mutant and wild type plants indicate that plant myrosinases reduced the glucosinolate sequestration rate by the insect in adult beetles [99]. Further analysis revealed that P. armoraciae can inactivate plant myrosinases in the gut to both reduce glucosinolate hydrolysis and promote their sequestering [99]. These findings indicate that adaptations of P. armoraciae to their brassicaceous host plants involve both the ability to tolerate plant myrosinase activity and a fast glucosinolate uptake mechanism.…”
Section: Countering and Exploiting The Mustard Oil Bomb By Pests And Pathogensmentioning
confidence: 99%
See 2 more Smart Citations